Incessant pericarditis as a risk factor for complicated pericarditis and hospital admission. (14th October 2021) - Imazio, M; Pivetta, E; Andreis, A; Serra, C; Ottino, M; Brucato, A; Giustetto, C; Rinaldi, M; Lupia, E; De Ferrari, G M; Adler, Y
Abstract: Background: Incessant pericarditis is defined as pericarditis with persistent symptoms without a symptom-free interval of 4 to 6 weeks despite therapy. On the contrary, recurrent pericarditis is characterized by recurring symptoms after a symptom-free interval of at least 4 to 6 weeks, allowing the completion of therapy. Aims: The aim of this study is to assess the risk of complicated pericarditis and related hospitalizations according to the clinical pattern of incessant or recurrent pericarditis. Methods: From January 2017 to December 2018, all consecutive patients admitted to AOU Città della Salute (Turin, IT) for pericarditis were included in a prospective cohort study with a clinical and echocardiographic follow-up at 1, 3, and 6 months, and then every 6 months. Results: We included 147 patients (median age, 50.9 years [IQR, 28.5]; 49.7% women, 89% had idiopathic aetiology, 11% had pericarditis related to systemic inflammatory disease/postcardiac injury syndrome, 80% had pericardial effusion, and 62% had elevated C-reactive protein >5 mg/L). Patients were treated according to ESC guidelines. After a median follow-up of 14 months (IQR, 9 months), adverse events were recorded in 54/147 patients (36.7%): nonidiopathic/viral aetiology in 16 of 147 cases (10.9%), recurrent pericarditis/persistent symptoms in 53 of 147 cases (36.1%), cardiac tamponade in 4/147 cases (2.7%), persistent CP in 4/147 cases (2.7%), and hospitalization related to pericarditis in 38/147 cases (25.9%). An incessant course was reported in 18 of 147 cases (12%). The risk of complications was higher in patients with incessant pericarditis (Figure) – especially CP – compared to nonincessant course (22.2% versus 0%, respectively; P<0.001). Patients with incessant pericarditis more commonly had echocardiographic evidence of CP (77.8% vs. 9.3%; P<0.001) and thickened pericardium on multimodality imaging (66.7% vs. 4.7%; P<0.001). These findings were reversible with medical therapy with the use of anakinra (100 mg/d) and colchicine in all but 4 cases that progressed to persistent CP, which were referred for pericardiectomy. An analysis of risk factors for complicated pericarditis and hospitalization using Cox proportional hazards regression analysis identified the following risk factors: large pericardial effusion (hazard ratio, 7.63 [95% CI, 3.09–18.83]), elevated C-reactive protein >5 mg/L (hazard ratio, 5.55 [95% CI, 1.87–16.44]), and incessant course (HR, 17.10 [95% CI, 7.63–38.33]). Conclusions: This study highlights that an incessant course of pericarditis is a possible new risk factor for complications and especially for developing constriction. In clinical practice, the detection of an incessant course, as well as imaging findings of constriction and pericardial thickening, should prompt more diagnostic testing, a close follow-up, and more aggressive therapy to prevent complications and persistent constriction. FUNDunding Acknowledgement: Type of funding sources: None.